The status and determinants of demoralization in patients with colorectal cancer: a cross-sectional study in China - Dan Zhou; Fanfan Shi; Jie Yang; Lili Jiang; Luo Yang; Jin Wen (Journal of Cancer Research and Clinical Oncology)
Abstract Background To investigate the occurrence and severity of demoralization syndrome (DS) in colorectal cancer (CRC) patients in China, and explore its influencing factors, so as to provide evidence for the formulation of psychological care strategies for colorectal cancer patients. Methods This study was a cross-sectional design. A questionnaire was formulated to investigate the demographic, disease characteristics and treatment information, demoralization syndrome, social support, anxiety and depression of patients, who treated in Colorectal Cancer Center of West China Hospital of Sichuan University from May to July 2023. t test, Wilcoxon rank sum test, Chi-square test or Fisher exact probability method were used for univariate analysis, and binary logistic regression analysis was used to explore the factors affecting demoralization syndrome. Results 445 colorectal cancer patients participated in this study, and the median score of demoralization syndrome was 10 (5–14), showing moderate demoralization syndrome. Univariate analysis showed that gender, tumor metastasis, social support, anxiety and depression might related to the severity of demoralization syndrome. Binary logistic regression showed, patients without tumor metastasis had a lower risk of developing moderate-to-severe demoralization syndrome compared with patients with tumor metastasis (OR = 0.522, 95%CI 0.319 ~ 0.848). The higher the anxiety and depression score, the higher the risk of moderate to severe demoralization syndrome (OR = 1.490, 95%CI 1.349 ~ 1.657, and OR = 1.167, 95%CI 1.073 ~ 1.272), P < 0.001. Conclusions It is necessary to consider the disease characteristics of colorectal cancer patients and the impact of treatment on patients to develop psychological nursing strategies comprehensively.